Human embryoid bodies as a 3D tissue model of the extracellular matrix and α-dystroglycanopathies - Nickolls, Alec R. (Dis Model Mech, 2020)
The basal lamina is a specialized sheet of dense extracellular matrix (ECM) linked to the plasma membrane of specific cell types in their tissue context, which serves as a structural scaffold for organ genesis and maintenance. Disruption of the basal lamina and its functions is central to many disease processes, including cancer metastasis, kidney disease, eye disease, muscular dystrophies and specific types of brain malformation. The latter three pathologies occur in the α-dystroglycanopathies, which are caused by dysfunction of the ECM receptor α-dystroglycan. However, opportunities to study the basal lamina in various human disease tissues are restricted owing to its limited accessibility. Here, we report the generation of embryoid bodies from human induced pluripotent stem cells that model the basal lamina. Embryoid bodies cultured via this protocol mimic pre-gastrulation embryonic development, consisting of an epithelial core surrounded by a basal lamina and a peripheral layer of ECM-secreting endoderm. In α-dystroglycanopathy patient embryoid bodies, electron and fluorescence microscopy reveal ultrastructural basal lamina defects and reduced ECM accumulation. By starting from patient-derived cells, these results establish a method for the in vitro synthesis of patient-specific basal lamina and recapitulate disease-relevant ECM defects seen in the α-dystroglycanopathies. Finally, we apply this system to evaluate an experimental ribitol supplement therapy on genetically diverse α-dystroglycanopathy patient samples. This article has an associated First Person interview with the first author of the paper.